Synthesis and physical-chemical properties of some 5-(3-fluorophenyl)-4-methyl-1,2,4-triazole-3-thiol derivatives - O. A. Bihdan; V. V. Parchenko (The State Expert Center of the Ministry of Health of Ukraine, 2018)
There are engaged scientists practically from all over the world to the 1,2,4-triazole system research but the greatest attention deserve the achievements of domestic scientists who managed from the very beginning to register new original medicines in Ukraine. There is no doubt that the original attempt of combining various typical fragments with the nucleus of 1,2,4-triazole is gaining popularity among researchers. The purpose of our work was to synthesized and investigate a row of new 5-(3-fluorophenyl)-4-methyl-1,2,4-triazole-3-thiols by a Sulfur atom, to study the physical-chemical properties of previously unsubscribed compounds. The chemical names of the compounds are given in accordance with the IUPAC nomenclature (1979) and the IUPAC recommendations (1993). Investigations of the physical-chemical properties of the obtained compounds were carried out according to the methods which are given in the State Pharmacopoeia of Ukraine. The melting point was determined on an automatic device for determining the melting point OptiMelt Stanford Research Systems MPA100 (USA). The elemental structure of the new compounds was established on the element analyzer Elementar Vario L cube (CHNS) (standard - sulfanilamide). The data of elemental analysis correspond to the calculated. The 1Н NMR-spectra of the compounds were recorded using a «Mercury 400» spectrometer, the solvent DMSO-d6, the internal standard - tetramethylsilane (TMS) and decrypted using the SpinWorks computer program. Chromate-mass spectra were recorded on an Agilent 6890N/5973N/FID spectrometer produced by Agilent Technologies with a Dean microflow switch. By the experiment results there were obtained eleven previously unidentified individual compounds light yellow and white color which are soluble in organic solvents and insoluble in water. The crystallization process was carried out in isopropanol. Using a complex approach with the use of modern physical-chemical methods of analysis we confirmed the structure of 5-(3-fluorophenyl)-4-methyl-1,2,4-triazole-3-thiol, 3-alkylthio-5-(3-fluorophenyl)-4-methyl-1,2,4-triazole, 1,4-bis((5-(3-fluorophenyl)-4-methyl-1,2,4-triazole-3-yl)thio)propane and 1,4-bis((5-(3-fluorophenyl)-4-methyl-1,2,4-triazole-3-yl)thio)butane. The individuality of the synthesized compounds was confirmed chromatographically, the constants peaks of the pseudo molecular ions of the synthesized compounds coincide with the calculated values of the molecular masses. We first synthesized 5-(3-fluorophenyl)-4-methyl-1,2,4-triazol-3-thiol which was further used as a starting material in the synthesis of new 3-alkylthio-5-(3-fluorophenyl)-4-methyl-1,2,4-triazole, 1,4-bis((5-(3-fluorophenyl)-4-methyl-1,2,4-triazol-3-yl)thio)propane and 1,4-bis((5-(3-fluorophenyl)-4-methyl-1,2,4-triazol-3-yl)thio)butane. Complex physical-chemical methods of analysis confirmed the structure of synthesized compounds.